AN APPROACH TOWARDS ETHICAL BODY: Relativizing Social and Religious Morals in Chinese History - Xin Zhang; Lei Zhang (Journal of Dharma, 2024)
This paper focusses on the missionary enterprises within the Chinese territory. Some scholars have argued that the purpose of these missionaries was to reinvent China based on western ideas, architecture, culture, etc. To reorient the ethical model from cultural and identity crises, this paper has employed the frameworks of Albert Memmi and Gayatri Chakravorty Spivak. To steer this missiological journey for the benefit of communities, the study approaches the entire expedition from an ethical standpoint. Simultaneously, it utilizes St. Paul’s analogy of the ethical body—reflecting the image of God and the body of Christ—to address and resolve contemporary issues in China.